Agency, structure, and the dominance of OEMs : Change and stability in the automotive sector - Jacobides, Michael G.; MacDuffie, John Paul; Tae, C. Jennifer (Strategic Management Journal, 2016)
Research summary: This article reviews structural change in the automotive sector from 1997 to 2007. We find that, following internal framing contests, O riginal E quipment M anufacturers ( OEMs) led efforts to change their sector's architecture, starting from both strong and weak competitive positions and working with suppliers to advocate a new vision based on modularity and outsourcing. As the risks and costs of this vision became apparent, OEMs were able to reverse course and reaffirm their hierarchical control on the sector, taking advantage of structural features that weren't salient ex ante. We consider why certain OEMs initiated this status‐quo challenging change, and identify how sector structure mediated their (and suppliers') efforts to implement it. We document the complex change process, driven by agency, structure, and heterogeneity in firms' understanding of their sector's architecture . Managerial summary: We study the “industry architecture” (i.e., division of labor and profit) of the automotive sector. During the late 1990s, O riginal E quipment M anufacturers ( OEMs) embraced a new vision, based on “ M odularity + O utsourcing,” inspired by an analogy with Personal Computers (PCs). This seems puzzling since such a change was hard to implement and could have led to OEMs relinquishing strategic control of the sector. The misstep was caused by internal framing contests and the agendas and influence of suppliers, consultants, and academics. We also consider why OEMs were able to partially reverse these changes, and document the role of structural features that let them control their sector and retain value: managing the customer experience, acting as guarantors of quality, and preserving hierarchical supply chains in which they functioned as system integrators . Copyright © 2015 John Wiley & Sons, Ltd.